Chemical synthesis of an indomethacin ester prodrug and its metabolic activation by human carboxylesterase 1. Issue 6 (1st April 2018) - Takahashi, Masato; Ogawa, Tomohiro; Kashiwagi, Hiroshi; Fukushima, Fumiya; Yoshitsugu, Misaki; Haba, Masami; Hosokawa, Masakiyo
Graphical abstract: Abstract: It is necessary to consider the affinity of prodrugs for metabolic enzymes for efficient activation of the prodrugs in the body. Although many prodrugs have been synthesized with consideration of these chemical properties, there has been little study on the design of a structure with consideration of biological properties such as substrate recognition ability of metabolic enzymes. In this report, chemical synthesis and evaluation of indomethacin prodrugs metabolically activated by human carboxylesterase 1 (hCES1) are described. The synthesized prodrugs were subjected to hydrolysis reactions in solutions of human liver microsomes (HLM), human intestine microsomes (HIM) and hCES1, and the hydrolytic parameters were investigated to evaluate the hydrolytic rates of these prodrugs and to elucidate the substrate recognition ability of hCES1. It was found that the hydrolytic rates greatly change depending on the steric hindrance and stereochemistry of the ester in HLM, HIM and hCES1 solutions. Furthermore, in a hydrolysis reaction catalyzed by hCES1, the Vmax value of n -butyl thioester with chemically high reactivity was significantly lower than that of n -butyl ester.